The president in Lithuanian political system: Search for position and power - Lukošaitis, Alvidas (Politologija, 1998)
Appeal of the Government to the Constitutional Court dated December 17, 1997, was aimed at judging whether the ruling of Seimas „On the Agenda of the Government of the Republic of Lithuania" dated December 10, 1997, went in no counteraction to the Constitution of the Republic of Lithuania. This appeal portrayed ambiguousness, which exists in relations between the legislative (Seimas) and the executive (President and Government) branches of Government. Ruling of the Constitutional Court January 10, 1998, interprets and rationalises, first, some of the Constitutional norms and, second, delineates guises of the political situation, which have crystallised in the aftermath of the elections. The ruling of the Constitutional Court emphasises that the pattern of the Lithuanian Government best conforms to the requisites of the parliamentary regime. In addition, the ruling regulates that the shape of the Lithuanian Government „has attained some uniformity with the so-called mixed (semi-presidential) mode of governance. This becomes reflected, [first], in the competence as delegated to Seimas, the President of the Republic, and the Government, and, [second], in the legal construction of their mutual dealings," - says the ruling of the Constitutional Court. Term „semi-presidential regime" was first employed by Maurice Duverger in his attempt to illustrate the type of the French political system (Fifth Republic). Furthermore, the majority of the post-communist countries might be more or less fraternised with the family of such a category of states. In fact, while picking out the future design of their political system, the post-communist states of the East European region faced two possible options - French semi-presidential and German parliamentary models. It seems that the Lithuania-state, on the other hand, was the sole of the post-communist states, which has settled attempts in adapting the shape of the American presidential regime in 1992. M.S. Shugart and J.M. Carey, in their analysis of the modes of Governance, sequester two types of the semi-presidential regime: „Premier - presidentialism" and „President - parliamentarism." The „Premier - presidential" model, according to them, encompasses the following characteristics: 1) universal way of electing the President; 2) considerable powers of the president - that is, legislative, „extraordinary," etc. powers; the president deploys the right to nominate the prime-minister and, perhaps, some other ministers; 3) there also subsist the Premier and the Government, who are the subjects of the parliamentary confidence; 4) the President has the right (with, or without, limitations applied) to dissolve the Parliament (however, he has no right to dismiss the Government unless the Parliament agrees). This model is best conformed by the Fifth French Republic. In the „President - parliamentary" system, authors claim, the President is likewise elected at the universal suffrage and he has the right to dissolve the parliament. However, the main disparities in these two former models concern the situation when the President has acquired further political power - likewise the latter model - in naming the Government: on his own discretion, he can assemble, modify the structure of the Government, appoint ministers. Meanwhile, the Parliament is given the right to consider the vote of confidence over the Government or the Prime Minister (according to the authors, the situation when both the Parliament and the President are given this „dual" right to decide upon the future of the Government forebodes conflictuality amidst the Parliament and the President). Examples of such a model - Sri Lanka since 1977 and the German Weimar Republic (1919 - 1933). The ground for such a classification rests in the bestowal of priorities which take place while delineating the powers of the President and the Parliament. In the case of the „Premier-presidential" model, a great deal of powers are delegated to the Parliament and, consequently, to the Government that is chaired by the Prime Minister; whereas in the case of the „President-parliamentarian" model, the pivotal bulk of powers is forwarded to the President. Thus, M.S. Shugart and J.M. Carey theorise the requisites of, first, the Presidential system: maximum powers of the President and austere separation of the branches of Government; second, characteristics of the „Premier-presidential" system: minimal Presidential powers and least separation of the branches of Government; and last, characteristics of the „President-parliamentarian" system, namely, maximum powers of the President in construing the Government in addition to minimum separation of the branches of Government. At the same time, M.S. Shugart distinguishes one extra type of regime, which has common traits with both the two aforementioned types of semi-presidentialism and the parliamentary system. M.S. Shugart calls this system (perhaps not so much the system, but its „option") „Parliamentary system with the President," who is elected by universal suffrage. This system bequeaths the following traits: a) the President is elected by universal suffrage; however, he b) does not dispose of independent rights in the process of construing the Government, c) he has no power of dissolution over the Government, and d) he hasn’t got any legislative powers (power to initiate the laws, plus veto). According to M.S. Shugart, Ireland is an example of this model. Of course, this is only a theoretical construction of the differences which are characteristic of a semi-presidential regime. In fact, practice may reveal far more complexities. For instance, might Lithuania be ascribed to the „Premier-presidential" regime (France) even in spite of the existing aberrations with the aforementioned characteristics? Herein, the system of electing the President of Lithuania, his and Seimas’ powers in ratifying the Government correspond to the criteria mentioned above. Yet, the powers of the President of the Republic, for instance, are far more limited than those of the French head of state—in practice, he has no formal opportunities to directly lead the work of the Government, even though the Constitution mentions the chance of this (Article 96, i.e.). On the other hand, in „Premier-presidential" regimes, Prime Ministers dispose of far more powers than in Lithuania. Moreover, such systems elucidate premier-dominant tendencies. For example, in respect to some specific circumstances, the Prime Minister, not the Chairman (President) of the Parliament, substitutes for the President; once and often, the Parliament consolidates the Executive and at the same time controls it; as a matter of fact, in the majority of countries, the seat of Premier, not the one of the Chairman of the Parliament, acts as the last lightning post on the path to the Presidential office, etc. In Lithuania, on the contrary, the Parliament encroaches upon the dominant political role and resists every effort to swing the political centre from the legislative to the executive branch. For instance, it is the Chairman of the Parliament who, due to specific circumstances, and instead of the Prime Minister, substitutes for the President; he signs the Laws which were vetoed or repeatedly passed by Seimas, etc. At the same time, Lithuania’s system of Governance contrasts the model characteristic of Ireland, namely, "parliamentary system with the President," because our President has obtained broad legislative powers. Therefore, it seems that Lithuania’s system of Governance, even despite the fairly large number of in-common traits with the French and Irish systems, is a unique phenomenon within the family of semi-presidential states, which, besides, has few analogues. Perhaps, it may instead be defined as a "parliamentary system with a fairly-powerful President." Nonetheless, having made estimations in accordance with M.S. Shugart’s categories, Lithuania might fit into parliament-presidentialism. Beyond doubt, the acting model of Lithuanian Governance is more intrinsic with parliamentarism, not presidentialism. The construction of the President, Seimas, and Government’s powers, as delineated in the Constitution, clearly shows that the priority was certified within the parliament, not the President. In its turn, the Constitutional Court of Lithuania was used to considering legal questions with less attention paid to political aspects. Was that inscribed to the competence of the Court to, let’s say, judge that "the Government must resign as the new President is elected" and that, for example, in the aftermath of this "the President names the Prime Minister and regulates him to construe the new Government," if the Constitution does not say that? Isn’t this an overt example when the Court is asked a question it may not be competent to answer? We all know that the sphere where the Constitutional Court is allowed to drift is severely limited: the Constitutional Court interprets the Constitution, not creates. The Constitutional Court, in its turn, had no such a right to state whether Lithuania is a Presidential, not a parliamentary, Republic "with several requisites of the mixed (semi-presidential) mode of Governance." In fact, this was the very first time we have seriously encountered the principles of such a model. One of these—corresponding alteration of the powers of the President and the Parliament as the balance of the parliamentary political forces shifts. This time it becomes obvious that the initiative will rest in the hands of the parliament; unless another composition of political forces in Seimas, the situation may counteract, and the President, potentially, can derive farther opportunities for action, and even expand the powers as inscribed in the Constitution. The course of the election campaign, brought together with the ruling of the Constitutional Court, led the problem of the President’s powers to the forefront. In the opinion of one side, the Lithuanian President is "powerful" enough; thus everything ought to be kept in status quo. According to others, he is too scantily empowered and "the means in order to modify the situation need become implemented." In other words, two options seem possible: either abdication from the decision of the Constitutional Court, or, what seems too clumsy, initiatives forwarding to the modification of the Articles of the Constitution which concern the powers of the President. Alas, today it is difficult to let one associate with them. Taking the first example, the principles of Constitutional stability might be violated (this, as we know, is a very acute problem for the countries which are yet in transition); thus the second example is doubtful either, and first of all, because of the short-lived Constitutional practice. Thus, it is the time which would let us answer yet another question, namely, whether it is rational to have the President who, on one hand, is elected by universal suffrage and who still has umbrageous powers, which, on their turn, are destined not only by the Constitutional norms, but by other factors as well.